VINAY AND DARBELNET’S TRANSLATING PROCEDURES USED IN TRANSLATING: ‘THE VILLAGE LEADER’ CHILDREN’S SHORT STORY BY ALYSSON CURRO - NOFATHANA SUPATRA; TIARA PANGESTUTI; SELI RAHMAWATI; NITA LESTARI (LINGUISTICA, 2024)
This study analyzed the translation procedures used in the translation of the children's short story "The Village Leader" from English to Indonesian. The study found that literal translation was the only translation procedure used in the translation of the story. Literal translation is a direct translation procedure that translates word-by-word processes with consideration towards the grammar and idiomatic structures from the source language to the target language. The high frequency of literal translation usage in this study suggests its importance in maintaining the original meaning and context of the story, ensuring that the translated version is easily understood by the target audience, especially children. The study highlights the importance of translation in bridging linguistic and cultural gaps, especially in the context of children's literature. The research method used in the study, which involved qualitative analysis and content analysis, was appropriate for in-depth understanding of the messages, values, and social context contained in the story.